The impact of crises in the 21 st century on the railway transport sector in Poland in terms of economic security - Latosiewicz, Dariusz; Kozicki, Bartosz; Magniszewski, Marek; Tołwiński, Maciej (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
The article presents research on the impact of the financial crisis between 2007-2009 and the COVID-19 pandemic in 2020 on the freight and passenger rail transport sector. Multidimensional comparative analyses were used in the study. The data obtained for the research were grouped. They were, then, compiled on categorized line and bar charts. The research shows that during the financial crisis between 2007-2009, a decrease in the number of transported goods by 48 488 thousand tons was observed. During the COVID-19 pandemic between 2019 and 2020, a decrease in the number of goods was also visible - by 15,363 tones. However, when considering the number of passengers transported, during the financial crisis between 2007-2009 in Poland there was an increase by 1,928 people and in the period of impact of COVID-19 in 2020 compared to 2019 a decrease by 130,270 passengers. When examining the rail passenger transport sector in Poland, a decrease in the number of employees by 385 was observed in the years 2003-2021. During the financial crisis between 2007-2009, the number of employees increased by 5,745 people, while during the COVID-19 pandemic in 2020, compared to 2019, it decreased by 109. In the case of the rail passenger transport sector in Poland, the number of employees oscillated around the arithmetic mean of 23,914 employees. Between 2003-2007, a downward trend can be observed, followed by a visible increase in 2008 and a downward trend in subsequent years.

W artykule przeprowadzono badania dotyczące wpływu kryzysu finansowego w latach 2007-2009 oraz pandemii COVID-19 w 2020 roku na sektor transportu kolejowego towarowego i pasażerskiego. W opracowaniu zastosowano wielowymiarowe analizy porównawcze. Pozyskane do badań dane poddano grupowaniu. Następnie zestawiano je na skategoryzowanych wykresach liniowych i słupkowych. Z przeprowadzonych badań wynika, że w czasie kryzysu finansowego pomiędzy 2007 a 2009 rokiem zaobserwowano spadek liczby przewiezionych towarów o 48 488 tys. ton. W okresie pandemii COVID-19 pomiędzy 2019 i 2020 rokiem również widoczny był spadek liczby towarów ‒ o 15 363 tys. ton. Natomiast rozpatrując liczbę przewiezionych pasażerów, w czasie kryzysu finansowego pomiędzy 2007 a 2009 rokiem w Polsce nastąpił wzrost o 1928 osób, a w okresie oddziaływania COVID-19 w 2020 w porównaniu do 2019 roku spadek o 130 270 pasażerów. Badając sektor pasażerskiego transportu kolejowego w Polsce, zaobserwowano w latach 2003-2021 spadek liczby zatrudnionych o 385 pracowników. W czasie kryzysu finansowego pomiędzy 2007 a 2009 rokiem odnotowano wzrost liczby zatrudnionych o 5745 osób, natomiast w czasie pandemii COVID-19 w 2020 roku w porównaniu do 2019 roku spadek o 109. W przypadku sektora pasażerskiego transportu kolejowego w Polsce liczba zatrudnionych oscylowała wokół średniej arytmetycznej 23 914 pracowników. W latach 2003-2007 zaobserwować można trend malejący, a następnie w 2008 roku silny wzrost i w kolejnych latach tendencję malejącą.
Wpływ kryzysów w XXI wieku na sektor transportu kolejowego w Polsce w aspekcie zachowania bezpieczeństwa ekonomicznego
Keywords: transport; rail transport; COVID-19; financial crisis; multidimensional data analysis; transport kolejowy; kryzys finansowy; wielowymiarowa analiza danych